A Novel Approach to Project Employee’s Performance and Confinement - N. Sandhya, G. Shirisha, M. Raja Sekar, (Design Engineering, 2021)
Employees are an organization’s most precious asset. The graphical representation of anticipating pay is a process that attempts to builda computerised system that canfollow all daily salary growth graphs in any location and predict revenue after a certain period of time.This application may access the company’s staff database and generate a graph based on the information contained therein. Before importing a graph to aid in the visual representation, it will validate the fields. Every company devotes time and resources to grooming new workers and preparing them for the workplace. If such individuals leave after completing their training, the company will suffer a complete loss.Most businesses assess retention rates on an annual basis, but you may measure it in smaller increments for speedier results. If it’s 80 percent, it signifies that just 20% of employees leave the company during a certain time period. Here we will compare and choose the best algorithm with accurate results and analysis.